Cation/Ca2+ Exchanger 1 (MdCCX1), a Plasma Membrane-Localized Na+ Transporter, Enhances Plant Salt Tolerance by Inhibiting Excessive Accumulation of Na+ and Reactive Oxygen Species - Yang, Jie; Li, Weihan; Guo, Xin; Chen, Peihong; Cheng, Yunpeng; Mao, Ke; Ma, Fengwang (Frontiers in Plant Science, 2021)
High salinity causes severe damage to plant growth and significantly reduces crop yields. The CCX family proteins can facilitate the transport of multiple ions to prevent toxicity. CCX proteins play an important role in regulating plant salt tolerance, but no detailed studies on CCX proteins in apples have been reported. Here, the CCX family gene MdCCX1 was cloned from apple (Malus domestica). It is constitutively expressed in various apple tissues and is significantly induced by salt stress. As a plasma membrane-localized protein, MdCCX1-overexpression could complement the Na+-sensitive phenotype of yeast mutants and reduce the Na+ content in yeast cells under NaCl treatment, suggesting that MdCCX1 could be a plasma membrane-localized Na+ transporter. To identify the function of MdCCX1 in salt response, we transformed this gene into Arabidopsis, apple calli, and apple plants. Overexpression of MdCCX1 significantly improved the salt tolerance of these transgenic materials. The significantly reduced Na+ content under NaCl treatment indicated that MdCCX1 overexpression could enhance plant salt tolerance by inhibiting the excessive accumulation of Na+. Besides, MdCCX1 overexpression could also enhance plant salt tolerance by promoting ROS scavenging. These findings provide new insight and rich resources for future studies of CCX proteins in plant species.